Plant-polyphenol-mediated synthesis of magnetic biocompatible iron oxide nanoparticles for diagnostic imaging and management of neurodegenerative diseases - Abdelmonem, Mohamed; Albert, Emmellie Laura; Alhadad, Maha A.; Che Abdullah, Che Azurahanim (Andover House, 2024)
Neurodegenerative diseases (NDDs), including Alzheimer’s disease (AD), Parkinson’s disease (PD), and glioblastoma tumors (GB), represent a spectrum of disorders characterized by progressive neuronal degeneration. This gradual deterioration presents significant challenges in early diagnosis and treatment. As a solution, iron oxide nanoparticles (IONPs) have emerged as promising materials due to their diminutive size and inherent biocompatibility, which facilitates bypassing the blood-brain barrier (BBB), thereby serving as effective targeted nanocarriers for neuroprotective therapeutics, offering efficient delivery to the brain. Furthermore, IONPs demonstrate efficacy as T1/T2 contrast agents (CAs), offering a novel diagnostic tool for various NDDs, emphasizing GB. Despite the expanding potential of IONPs in the management of NDDs, a clear gap exists in developing environmentally sustainable synthesis methods. Such methods must adhere to ecological standards and enable the production of nanoparticles capable of efficiently crossing the BBB. This is essential for precisely delivering and monitoring therapeutic interventions in diseases such as AD, PD, and GB. This review systematically explores the potential of green-synthesized IONPs in the context of NDD treatment. In this review, we emphasize different functionalization techniques for IONPs, tackling how these functionalized IONPs can be effective therapeutic approaches for NDDs. Moreover, we discuss biosafety and biocompatibility by covering a range of in vitro biocompatibility studies to analyze the safety of green-synthesized IONPs for the human body. Furthermore, our thorough analysis discussed the current state of greensynthesized IONPs using plant extracts polyphenols, which also act as neuroprotective agents, as proved by studies mentioned in the review.